Short Communication: The resistance of Styrax sumatrana wood of varying growth sites and stem axial positions to subterranean termite (Coptotermes curvignathus) attack - Apri Heri Iswanto; Joel Tambunan; arida Susilowati; Rudi Hartono; Atmawi Darwis (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Iswanto AH, Tambunan J, Susilowati A, Hartono R, Darwis A. 2021. Short Communication: The resistance of Styrax sumatrana wood of varying growth sites and stem axial positions to subterranean termite (Coptotermes curvignathus) attack. Biodiversitas 22: 3192-3198.  As mega-biodiversity country, Indonesia consists of a large number of flora and fauna, including wood-destroying organisms such as termites.  One of the native trees known as a resin producer is Tobanese incense (Styrax sumatrana). The existence of this species has been studied for several wood properties such as physical, mechanical, and chemical properties, while its natural durability against termite attack has not been studied. As a country known as a haven for termites, the study on incense wood durability is very important for further utilization.  The objective of this research was to analyze the natural durability of S. sumatrana wood from two growing locations and different stem positions using a graveyard test. The Graveyard test method was used to investigate the mass loss and percentage of damage of the sampled woods. The test sample used is 2x2x20 cm3 in size. The sample is buried as deep as 15 cm and leaving 5 cm of the part that is above the soil surface. The distance between the samples is 60 cm. The results obtained from this study indicated that the incense wood originating from Pakpak Bharat and North Tapanuli districts can be classified as durable class V (Vulnerable category) and severely damaged (E category) with the respective mass loss percentages ranging from 22.03-31.70% and 18.46-20.79% and damage percentages ranging from 86.55-96.27% and 78.02-86.32%. In conclusion, the positions of the stem and the sites where it grows caused a difference in the natural durability value of Styrax sumatrana wood. The incense wood originating from North Tapanuli District had slightly better durability against subterranean termite attacks than that from Pakpak Bharat District, although overall the samples from these two sites fell into the same durability class.